The End of the Political Subject Wars without Revolutions - Valentić, Tonči (Phainomena, 2024)
Badiou's work, entailing books, such as Metapolitics, Theoretical Writings, Being and Event, and Theory of the Subject, explores the complex connections between philosophy, politics, and subjectivity. Badiou's analysis shows how political subjects can be a force for change, challenging established power structures and opening the way to new forms of political action. [...]this article aims to provide an in-depth analysis of Badiou's philosophical thought, considering how his concepts and theories influence the understanding of the political subject, truth, subjectivity, and ontology. Badiou advocates for an ethics of truths, which supports a disciplined, subjective commitment to a militant cause (whether political, scientific, artistic, or romantic) and distinguishes a clearly defined zone of application of the concept of evil (Badiou 2001). Because of such conceptualizations, Badiou's philosophy was, and still is, very influential, and provides a deep analysis and understanding of political, artistic, scientific, and love processes, while challenging traditionalphilosophical paradigms.